The PENATALAKSANAAN HOLISTIK PEREMPUAN USIA 41 TAHUN DENGAN HIPERTENSI DERAJAT II, DISPEPSIA, DAN VERTIGO MELALUI PENDEKATAN KEDOKTERAN KELUARGA DI WILAYAH KERJA PUSKESMAS NATAR - Fadillah Maulidia; Azelia Nusadewiarti (Medula, 2023)
Hypertension is one of the non-communicable diseases (PTM) which is a very serious health problem both in the world and in Indonesia and is the cause of death which reaches 6.7% of the population at all ages in Indonesia. Dyspepsia is a health problem that is often encountered in daily practice. It is estimated that nearly 30% of cases found in general practice and 60% in gastroenterology practice are dyspepsia. A 41-year-old female patient came to the health center with complaints of dizziness, nausea, vomiting and cold sweat. The patient has a history of hypertension since 2013. In addition, patients also often complain of pain in the pit of the stomach. Complaints are felt repeatedly. Patients do not routinely take antihypertensive medication and do not routinely control and do not follow a healthy lifestyle. Patients have a desire to know more about the patient's illness and want to recover. The patient's knowledge about the disease is lacking, as well as curative treatment patterns, poor diet, rarely exercise and moderate physical activity. Diagnosis and management of these patients has been carried out in a holistic, patient-centered, family approach based on evidence-based medicine and there have been changes in the knowledge and behavior of patients and families after the intervention.